Growth hormone protects against kainate excitotoxicity and induces BDNF and NT3 expression in chicken neuroretinal cells. (January 2018) - Martinez-Moreno, C.G.; Fleming, T.; Carranza, M.; Ávila-Mendoza, J.; Luna, M.; Harvey, S.; Arámburo, C.
Abstract: There is increasing evidence to suggest a beneficial neuroprotective effect of growth hormone (GH) in the nervous system. While our previous studies have largely focused on retinal ganglion cells (RGCs), we have also found conclusive evidence of a pro-survival effect of GH in cells of the inner nuclear layer (INL) as well as a protective effect on the dendritic trees of the inner plexiform layer (IPL) in the retina. The administration of GH in primary neuroretinal cell cultures protected and induced neural outgrowths. Our results, both in vitro (embryo) and in vivo (postnatal), showed neuroprotective actions of GH against kainic acid (KA)-induced excitotoxicity in the chicken neuroretina. Intravitreal injections of GH restored brain derived neurotrophic factor (BDNF) expression in retinas treated with KA. In addition, we demonstrated that GH over-expression and exogenous administration increased BDNF and neurotrophin-3 (NT3) gene expression in embryonic neuroretinal cells. Thus, GH neuroprotective actions in neural tissues may be mediated by a complex cascade of neurotrophins and growth factors which have been classically related to damage prevention and neuroretinal tissue repair. Highlights: GH has neuroprotective actions against KA-induced injury in retinal cell cultures. GH induces growth and protection on neurites in embryonic neuroretinal cells. Short-term incubations with GH induces an increase of BDNF and NT3 mRNA in vitro. Intravitreal injections of GH reduce KA-excitotoxic damage in postnatal retinas in vivo. Intravitreal GH treatment restores BNDF to normal levels after excitotoxic damage.